METODE PEMBUKTIAN TEOREMA CAYLEY PADA TEORI GRAPH - Abdullah, Abdul Wahab (Sainstek, 2009)
This article describes two methods to prove Cayley Theorem in Graph Theory, through 1-1 corespondence between labelled tree - sequence and through Combinatorial Theory. Kata Kunci : Graph Theory, Combinatorial Theory, corespondence 1-1, labelled tree, Cayley Theorem